Development Of Cream Crackers Containing Coconut Palm Sugar: Nutritional Composition And Sensory Analysis - Ooi, Jia Yi (Universiti Sains Malaysia, 2020)
Coconut palm sugar can be used as a natural sweetener in various food. This study aimed at developing cream cracker using genuine coconut palm sugar. Besides, this study also determined the effect of coconut palm sugar on the proximate, texture profile and consumer acceptability of developed cream cracker. In this study, genuine coconut palm sugar was used to substitute the usage of white sugar at 0% (control), 50% and 100% ratio in the formulation of cream crackers. Cream crackers incorporated with coconut palm sugar were investigated for their nutritional composition, physical properties and sensory properties. Proximate analysis of cream crackers was carried out, and cream crackers with 100% coconut palm sugar substitution showed significantly higher (p < 0.05) moisture (3.23%), protein (12.08%), ash (2.84%) and carbohydrates content (70.30%) with lower fat (12.55%) than control. In terms of physical characteristics, incorporation of 100% coconut palm sugar into cream crackers showed lowest value in lightness (L*) and highest value in a* and b*. Besides, 100% substitution levels of coconut palm sugar also decreased the hardness of cream crackers (p < 0.05). Sensory evaluation revealed that formulated cream crackers (100% coconut palm sugar) received the highest score values in terms of aroma, taste, texture and overall acceptability, but lowest score values in terms of colour. Coconut palm sugar could be used as a raw ingredient for developing cream crackers.